1981 Report of Agricultural Research, Southeast Kansas Branch Station - K. W. Kelley; L. W. Lomas; J. L. Moyer; R. E. Lamond (Kansas Agricultural Experiment Station Research Reports, 1981)
This annual research report is to inform area farmers of what is being attempted and accomplished at the Southeast Kansas Branch Experiment Station to serve the area. During 1980 the Station headquarters was moved from Mound Valley to Parsons, the location of one of the units of the Station since 1967. Effort at the Mound Valley location continues without reduction. The third unit of the Station is near Columbus. This report covers four areas of research emphasis: crops, forages, beef cattle, and soil and water management. The information is intended for producers, industry cooperators, and other interested persons.
Keywords: corn; grain sorghum; soybeans; wheat; alfalfa; forage; beef cattle; soil; water management